2006
DOI: 10.2172/888663
|View full text |Cite
|
Sign up to set email alerts
|

Wettability and Oil Recovery by Imbibition and Viscous Displacement from Fractured and Heterogeneous Carbonates

Abstract: About one-half of U.S. oil reserves are held in carbonate formations. The remaining oil in carbonate reservoirs is regarded as the major domestic target for improved oil recovery. Carbonate reservoirs are often fractured and have great complexity even at the core scale. Formation evaluation and prediction is often subject to great uncertainty. This study addresses quantification of crude oil/brine/rock interactions and the impact of reservoir heterogeneity on oil recovery by spontaneous imbibition and viscous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Much of the pore space is moldic, having formed through the preferential dissolution of fossil pieces. This contributes to the overall complexity of the pore network (Morrow & Buckley, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Much of the pore space is moldic, having formed through the preferential dissolution of fossil pieces. This contributes to the overall complexity of the pore network (Morrow & Buckley, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…McGuire et al [ 2 ] identified brine solutions with salt concentrations below 5000 ppm as optimal for achieving up to 19% additional oil recovery. Morrow and Buckley [ 3 ] experimented with using various crude oils acquired from different reservoirs, considering asphaltenes content and acidic/basic type to comprehend wettability alteration of the rock surface. The authors successfully controlled wettability through different crude oil compositions.…”
Section: Introductionmentioning
confidence: 99%